1995
DOI: 10.1089/ten.1995.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of PLA-PGA Orthopedic Implants

Abstract: Fabrication methods and property characterization of polyglycolic acid (PGA), polylactic acid (PLA), and their copolymers are reviewed. Both of these aliphatic polyesters belong to the a-hydroxy group and biodegrade in a physiological environment to monomeric acids, which are readily processed and excreted from the body. The physical and mechanical characteristics discussed include molecular weight, crystallinity, stress-strain behavior, permeability, and melting/glass transition temperatures. The most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 55 publications
0
36
0
1
Order By: Relevance
“…Biodegradable poly(α-hydroxy ester) polymers, including poly(lactide-co-glycolide) (PLAGA), have been used extensively for fabrication of 3D scaffold biomaterials utilized in tissue engineering due to their commercial availability, excellent biocompatibility, and prior FDA approval for a number of clinical applications [43]. These synthetic biomaterials can circumvent limitations of systemic delivery by sustaining release and bioavailability of a growth factor within target tissues without systemic and/or dose-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradable poly(α-hydroxy ester) polymers, including poly(lactide-co-glycolide) (PLAGA), have been used extensively for fabrication of 3D scaffold biomaterials utilized in tissue engineering due to their commercial availability, excellent biocompatibility, and prior FDA approval for a number of clinical applications [43]. These synthetic biomaterials can circumvent limitations of systemic delivery by sustaining release and bioavailability of a growth factor within target tissues without systemic and/or dose-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done on rats, the PLA implants were labeled with radioactive carbon and placed internally in rats for 3 months, as a result there was no significant radio activity found in the urine or feces, which confirmed that the polymer is degraded and probably eliminated through CO 2 during respiration. Further, PGA can be broken down in two ways, by hydrolysis sand by nonspecific esterase and carboxypeptidases (Agrawal et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the PLA is used as a biopolymer, which would biodegradable and is nontoxic to humans. Another reason is that, PLA could be fermented easily using natural fermentation process, thus it is considerably low cost compared few metal implants (Agrawal et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Polymers belonging to the PLA-PGA family are now widely used for fabricating implantable drug delivery systems and fracture fixation devices for orthopedics applications. 17 These materials are popular because they are reasonably biocompatible 18 and their structure-property relationships have been examined in detail. [19][20][21] In addition, their in vivo and in vitro biodegradation characteristics also have been studied extensively.…”
Section: Methodsmentioning
confidence: 99%